Diagnosis and Management for Pulmonary Tuberculoma - Syahruddin, Elisna; Burhan, Erlina; Saputra, Tetra Arya (Respiratory Science, 2024)
Pulmonary tuberculoma, prevalent particularly in tuberculosis (TB)-endemic regions, often appears as a solitary nodule of less than 30 mm, or a tumor of more than 30 mm on radiological examinations. It may also present with a combination of abnormalities, such as multiple nodules with infiltration or pleuritis. Benign solitary pulmonary nodules represent up to 25% of all resected solitary pulmonary nodules, with approximately 5-24% of these identified as pulmonary tuberculoma post-surgery. This condition is prevalent particularly in TB-endemic regions, and must be considered while determining the diagnosis, especially for patients at high risk for lung cancer. Modalities for diagnosing pulmonary tuberculoma include chest radiography, USG, CT scan, PET scan and bronchoscopy with transbronchial biopsy. The treatments for pulmonary tuberculoma are anti-TB drugs and surgery. Pulmonary tuberculoma responds poorly to anti-TB drugs and requires long-term treatment. Surgery is performed when the diameter of tuberculoma still increases after adequate anti-TB treatment.